Effect of Maleic Anhydride Polypropylene on Flexural Properties of Hybrid Kenaf - Sugar Palm Fibre Reinforced Polypropylene Composites - Bachtiar, Dandi; Siregar, Januar Parlaungan; Iqbal, Mohd; Masri; Zulfadhli; Muhibbuddin (Journal of Engineering and Science, 2023)
This study was focused on the characterize the hibridisation of kenaf and sugar palm fibre in reinforcing the polypropylene matrix. Addition of MAPP (Maleic Anhydride Polypropylene) was used as compatibilizing agent with variation of 2%, 3% and 5%. The specimen materials were prepared with 30% amounts of fibres while the ratios between kenaf and sugar palm fibre are 10:20, 15:15 and 20:10. The composites were fabricated using melt mixer technique and followed by compression molding process. The specimens were cut according ASTM Standard D790 for conducting the flexural testing. After testing done, the results shown that flexural strength of composites tend to decreased when the content of MAPP increased. The ultimate flexural strength was attained at 2% MAPP addition of the hybrid composites with 20% kenaf fibres. Among the composites with different ratios, the hybrid composites that contain more kenaf fibres exhibit the higher value in flexural strength than the composites that contain more sugar palm fibres.